Entrevista com Warren Warbrick: a Cultura e os Sons Maori e a Integração Multicultural entre a América Latina e a Nova Zelândia (Revista Internacional de Folkcomunicação, 2020)
Considered one of New Zealand’s leading artists, Warren Warbrick is a musician who not only makes traditional Māori musical instruments but conducts research on them. He discusses the cultural importance of this music and as well as the multicultural relationship between New Zealand and Latin America, particularly Brazil. Warren Warbrick. Multiculturalism. New Zealand. Latin America. Brazil